Waste less time on Facebook — follow Brilliant.
×

Freshman's Dream!

\[\displaystyle \int_0^1 {x^{x^{x^{.^{.^.}}}} \ dx} = \sum_{k=0}^{\infty}{{(-1)}^k {(k+1)}^{k-1}}\]

Proof:

Since generalized exponential series -

\[\displaystyle \mathcal{E}_t(x) = \sum_{k = 0}^{\infty}{{(tk+1)}^{k-1} \frac{x^k}{k!}}\]

follow

\[\displaystyle \mathcal{E}_t(x) = \exp(x\mathcal{E}_t(x)^t)\]

Therefore, for \(t= 1\),

\[\displaystyle \mathcal{E}(x) = \exp(x\mathcal{E}(x))\]

\[\displaystyle \mathcal{E}(\ln(x)) = \exp(\mathcal{E}(\ln(x)) \ln(x)) = x^{\mathcal{E}(\ln(x))}\]

That's our tetration.

\[\displaystyle \mathcal{E}(\ln(x)) = x^{x^{x^{.^{.^.}}}}\]

Also,

\[\displaystyle \mathcal{E}(\ln(x)) = \sum_{k = 0}^{\infty}{{(k+1)}^{k-1} \frac{{\ln(x)}^k}{k!}}\]

\[\displaystyle \int_0^1{x^{x^{x^{.^{.^.}}}}\ dx} = \sum_{k = 0}^{\infty}{\frac{{(k+1)}^{k-1}}{k!} \int_0^1{{(\ln(x))}^k \ dx} } \]

Let's take this integral separately.

\[I = \int_0^1 {{(\ln(x)}^k\ dx}\]

Consider

\[I(n) = \int_0^1 {x^n \ dx} = \frac{1}{n+1}\]

\[I^{(k)}(0) = \int_0^1 {{(\ln(x)}^k\ dx} = {(-1)}^k k!\]

Therefore,

\[\displaystyle \int_0^1{x^{x^{x^{.^{.^.}}}}\ dx} = \sum_{k = 0}^{\infty}{\frac{{(k+1)}^{k-1}}{k!}{(-1)}^k k! } \]

\[\displaystyle \int_0^1 {x^{x^{x^{.^{.^.}}}} \ dx} = \sum_{k=0}^{\infty}{{(-1)}^k {(k+1)}^{k-1}}\]

/*

Now this "oscillating divergence" is really not what I liked. Is it correct, anyways?

I am not really freshman yet. Will be in a month or so.

*/

Note by Kartik Sharma
2 months, 3 weeks ago

No vote yet
1 vote

Comments

There are no comments in this discussion.

×

Problem Loading...

Note Loading...

Set Loading...